HEALTH RISK ASSESSMENT OF CHROMIUM IN ORGANS OF Synodontis clarias AND Clarias agboyiensis FROM EPE LAGOON, LAGOS, NIGERIA - EITOKPAH, E. P (Nigerian Journal of Fisheries, 2022)
Pollution of the aquatic ecosystems with mixtures of organic and inorganic compounds remains a recurrent problem of global concern due to their toxicity, bioaccumulation, and potential for adverse effects in biological systems. This study investigated the seasonal variation of accumulated chromium (Cr) in the organs of Synodontis clarias and Clarias agbobyiensis from Epe Lagoon, Lagos, Nigeria. The mean length and weight of Synodontis clarias collected during wet (33.52 ± 0.22 g and 28.40 ± 0.25 cm) and dry seasons (210.06 ± 3.67 g and 185.2 ± 2.54 cm) and Clarias agbobyiensis collected during wet (33.52 ± 0.22 g and 28.40 ± 0.25 cm) and dry season (210.06 ± 3.67 g and 185.2 ± 2.54 cm) between June 2014 and April 2016 were reported herein. Statistical analysis showed a significant increase (p<0.05) in accumulated heavy metals by Synodontis clarias and Clarias agbobyiensis in wet seasons. The calculated Hazard index (HI) in liver and gill was less than 1.0 which implied non-carcinogenic adverse effects from the consumption of these fish species. The HI was highest in the liver than the gill.